Assessing the effect on the mode of class attendance on academic performance in a postgraduate financial accounting IV class at a private higher education institution in South Africa - Gauldie, Nicola Claire (College of Accounting, 2025)
Public higher education institutions are at capacity in terms of their student intake. Therefore, there has been an increase in private higher education institutions providing options for students regarding the offered class attendance modes. However, not all modes will achieve an optimal output. Thus, the objective of this study was to determine which mode of class attendance, if any, improves the students' academic performance. The study was performed to determine if higher education institutions could increase their enrolment numbers through offering diverse class attendance modes, rather than the traditional face-to-face mode of instruction. The study was conducted at a private higher education institution on 231 post graduate Financial Accounting IV students. A quantitative analysis was performed using the beta regression analysis and the Kruskal-Wallis test. Additionally, machine learning in the form of the random forest algorithm technique was employed to alleviate the limiting effect of the small sample size. The class modes investigated were in-person attendance, streaming attendance and attendance of students who watched classes at a later date. Other additional factors, which included age, gender, race, undergraduate Accounting mark, undergraduate Accounting institution and time lapse since completion, were part of the analysis to mitigate the risk of incorrectly assuming an outcome. The findings of the beta regression analysis indicated that the most significant indicator of academic performance in Financial Accounting IV was full-time in-person attendance. Classes watched at a later date and flexi-streaming also proved to be significant in predicting the final academic outcome. Full-time streaming was still significant, but less so than the other factors. A noteworthy finding from the Kruskal–Wallis test was that there was no statistically significant difference in academic performance across the different class attendance modes, based on the students' primary mode of attendance. The study subjects were only postgraduate Accounting students from a private higher education institution and therefore, they differed from those in other higher education institutions in South Africa. This implied that the results are not generalisable. Nevertheless, the findings are useful to private higher education institutions in shaping their available class formats for postgraduate Accounting studies. The study contributes to the existing literature on tertiary Accounting education and factors that contribute to academic success.